The importance of implementing pollution prevention principle in effluent water management for environmental legal compliance in a coal power station, a case of Kendal Power Station, Mpumalanga Province, South Africa - Van Aardt, I. (University of Pretoria, 2022)
Mini Dissertation (MA (Environment and Society))--University of Pretoria, 2022.